Transitioning peanut oral immunotherapy to clinical practice - Lazizi, S.; Labrosse, R.; Graham, F. (Frontiers in Allergy, 2022)
Peanut allergy is on the rise in industrialized countries, affecting 1%–4.5% of children and generally persisting into adulthood. It is associated with a risk of severe anaphylaxis and is one of the major causes of food allergy-induced deaths. Health-related quality of life is significantly impaired for patients and affected families due to food restrictions attributable to omnipresent precautionary allergen labeling, constant risk of potentially life-threatening reactions, and limitation of social activities. Oral immunotherapy (OIT) has emerged as a valid treatment option for patients with IgE-mediated peanut allergy, with randomized controlled trials and real-life studies showing a high rate of desensitization and a favorable safety profile, especially in young children. Ultimately, the decision to initiate peanut OIT relies on a multidisciplinary shared decision-making process, involving open, personalized and evidence-based discussions with patients and their caregivers.